Analysis of water balance in the middle reaches of the Yellow River based on ecological water demand: A case study on Qinhe River Basin - Yi LIU; Peidong SHI; Miao LIU; Kairan XU; Ning ZHANG; Peng JIANG (Shuiwen dizhi gongcheng dizhi, 2024)
Analysis of water balance in the middle reaches of the Yellow River is important for the effective water resources management, ecological protection, and high-quality development in the Yellow River Basin. The Qinhe River Basin, located at the end of the middle reaches of the Yellow River, has serious water problems, such as, river interruption and insufficient inflow into the Yellow River, due to the implementation of the upstream water diversion policy and the increase in domestic and industrial water use. To address the water problems, the water resource demand, water supply capacity, and supply-demand balance of the basin were analyzed based on the ecological water demand. The results show that (1) the spatial distribution of water supply and water demand in the Qinhe River basin is heterogeneous. All the upstream river reaches in the Shanxi Province are able to guarantee the ecological water demand in the river channel, while in the downstream Henan Province, only the minimum water demand can be met; (2) the total suppliable water resources in the Qinhe River basin is 10.04×108 m3, and the sum of industrial, domestic, and ecological water use outside the river channel is 8.89×108 m3. The remaining water in the river channel is only 1.15×108 m3, which can only meet the minimum ecological water demand; (3) the amount of surface water used by industrial production and life in the basin will be 6.98×108 m3 in 2030, and the total amount of water use will be 9.81×108 m3, resulting in that the remaining water cannot support the minimum ecological water demand. We pose five suggestions for the water problem in the Qinhe River Basin: Reducing the industrial water consumption, improving the water utilization rate of agricultural irrigation, promoting water conservation technologies with high effectiveness, and improving the ecological environment. This study can provide basic information for the effective water resources management in the Qinhe River basin.